The phenotype, psychotype and genotype of bruxism - Cruz Fierro, Norma; Martínez Fierro, Margarita de la Luz; Cerda Flores, Ricardo Martín; Gómez Govea, Mayra Alejandra; Delgado Enciso, Iván; Martínez de Villarreal, Laura Elia; González Ramírez, Mónica Teresa; Rodríguez Sánchez, Irám Pablo (Spandidos Publications, 2018)
Abstract. Bruxism is a jaw muscle activity that involves physio-pathological, psycho-social, hereditary and genetic factors. The purpose of this study was to determine the associations between self-reported bruxism, anxiety, and neuroticism personality trait with the rs6313 polymorphism in the gene HTR2A. A sample of 171 subjects of both sexes (14-53 years of age) was included. The control group (group 1, n=60) exhibited no signs or symptoms of bruxism. The case group had signs and symptoms of bruxism (n=112) and was subdivided into group 2, bruxism during sleep (n=22); group 3, awake bruxism (n=44); and group 4 combined bruxism (n=46). As diagnostic tools, the Self-Reported Bruxism Questionnaire (SBQ), the Beck Anxiety Inventory (BAI) and the Eysenck Personality Questionnaire Revised-Abbreviated (EPQR-A) were used. HTR2A (rs6313) SNPs were determined by qPCR for all the participants. The packages SPSS, maxLik and EPI-INFO were used for data analysis. The combined bruxism group reported higher scores in bruxism symptoms, mean = 32.21; anxiety symptoms, mean = 14.80; and neuroticism, mean = 3.26. Combined bruxism was associated with a higher degree of neuroticism (OR=15.0; CI 1.52-148.32) and anxiety in grade 3-moderate (OR=3.56; CI 1.27-10.03), and grade 4-severe (OR=8.40; CI 1.45-48.61), as determined using EPISODE computer software. Genotypic homogeneity analysis revealed no significant differences in allele frequency (P=0.612) among the four groups. The population was in Hardy-Weinberg equilibrium (maxLik package). In conclusion, the three instruments confirm traits of bruxism, anxiety and neuroticism in individuals with bruxism. These data were ratified when the sample was divided by genotypic homogeneity. On the other hand, there was no significant difference between the groups in the SNPs rs6313 from the HTR2A gene.